Predictive Value of Anti-Müllerian Hormone for IVF Outcomes: A Study from Poissy Hospital, France - Mwakila, A. A.; Mboloko, E. J.; Ngoyi, K. D.; Likinda, I. G.; Mulinda, M. A.; Mogwo, S. P.; Moangi, B. C.; Bikuelo, B. C.; Mboloko, M. J. (Medical Science: Trends and Innovations Vol. 10, 2025)
Background: Anti-müllerian hormone (AMH) is a glycoprotein of gonadal origin belonging to the Transforming Growth Factor \(β\) family (TGF-\(β\)), secreted in women by granulosa cells. Assessment of ovarian reserve is an essential parameter in the evaluation of female infertility. It has been established that serum anti-müllerian hormone (AMH) is the best marker of ovarian reserve and predicts the quality of ovarian response to stimulation. However, there is some controversy about the prediction of pregnancy rates. Can the serum AMH assay predict the chances of successful In vitro fertilization (IVF)? Objective: To analyze the association between AMH levels, the number of mature oocytes obtained by oocyte puncture after stimulation and the outcome of In vitro fertilization at the first attempt. Methods: An analytical cross-sectional study with retrospective data collection on 123 patients who had consulted for a desire to conceive and undergone ovarian reserve evaluation followed by IVF in the assisted reproduction department of the Poissy-Saint-Germain-en-Laye Intercommunal Hospital Centre at its Poissy hospital site between January 2020 and March 2022. Results: Of the 123 patients, 43.8% had normal AMH levels. At the end of stimulation, almost half of patients (52.84%) had a sub-optimal ovarian response and almost a quarter had a poor response (27.64%). We found a statistically significant positive correlation [r = 0.42 b = 0.70 CI 95% (0.43 - 0.97) p = 0.000] between AMH level and the number of mature oocytes collected. Of all patients with low AMH, 83.3% had a clinical pregnancy, while 61.1% of patients with normal AMH had no pregnancy. These differences were statistically significant (p = 0.001). AMH level was significantly associated with predicting ovarian response to stimulation and had a decreasing association with IVF outcome. Indeed, compared with patients with low AMH levels, those with normal AMH levels were 7 times more likely to have a good response to stimulation [OR = 7.12 CI 95% (1.98 - 30.79) p = 0.003] and less likely to achieve pregnancy after embryo transfer. Conclusion: AMH assay is an important marker of ovarian reserve and predicts ovarian response to stimulation. It correlates with the number of mature oocytes that can be collected at puncture but does not predict the chances of IVF pregnancy. Therefore, unless constrained by the patient’s age, the AMH level should not justify a direct decision to donate oocytes; prior stimulation should be attempted.